2013
DOI: 10.1007/s00535-012-0731-8
|View full text |Cite
|
Sign up to set email alerts
|

Multi-center randomized controlled study to establish the standard third-line regimen for Helicobacter pylori eradication in Japan

Abstract: The findings suggest that triple therapy with PPI, AMPC, and STFX for one week would be an effective standard third-line eradication regimen for H. pylori in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
87
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 20 publications
3
87
0
Order By: Relevance
“…Unlike clarithromycin and metronidazole, amoxicillin resistance rates are low worldwide [30] : 0% or < 1% in Europe [30] . However, other studies revealed high amoxicillin resistance rates in Iran, Japan, and Cameroon [37,45,54] . Fluoroquinolones are the sole class of antibiotics for treatment of H. pylori that directly inhibit bacterial DNA synthesis.…”
Section: Current Antibiotic Resistance In Worldwidementioning
confidence: 90%
See 3 more Smart Citations
“…Unlike clarithromycin and metronidazole, amoxicillin resistance rates are low worldwide [30] : 0% or < 1% in Europe [30] . However, other studies revealed high amoxicillin resistance rates in Iran, Japan, and Cameroon [37,45,54] . Fluoroquinolones are the sole class of antibiotics for treatment of H. pylori that directly inhibit bacterial DNA synthesis.…”
Section: Current Antibiotic Resistance In Worldwidementioning
confidence: 90%
“…In a study published in Japan, the clarithromycin resistance rate in 2002 was 18.9%; however, the clarithromycin resistance rate in 2006 increased to 27.2% [36] . Even with third-line eradication therapy, clarithromycin resistance rates in Japan were reported as 86.4% [37] . Several studies in China have reported increased resistance rates Shanghai [38] , 21.5% resistance in the southeast coastal region [39] , and a relatively high rate of 33% in Vietnam, which is near Southeast China [40] .…”
Section: Current Antibiotic Resistance In Worldwidementioning
confidence: 99%
See 2 more Smart Citations
“…Comment: A Japanese RCT of third-line therapy showed that the eradication rate of triple therapy with sitafloxacin was 70 % [40]. Because the rate was not high enough, no regimens were recommended in this guideline.…”
Section: Third-line Eradication Therapymentioning
confidence: 99%